2023
DOI: 10.47278/journal.ijab/2023.058
|View full text |Cite
|
Sign up to set email alerts
|

The Consequences of Plant Architecture and Spatial Distribution of Light Interception on Cotton Growth and Yield

Abstract: The architecture of the canopy tends to affect how light is reflected and distributed within it. Rational modelling and trimming can improve crop architecture, maximize the use of space, light, and resources such as land, and lay the groundwork for initial maturing, and maximum yield. Determining the interception of light inside the canopy is critical aimed at increasing the population's photosynthetic production. By implementing cultural practices that produce optimal plant populations and alter the plant can… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 44 publications
0
2
0
Order By: Relevance
“…It is widely accepted fact that stomatal closure by these stresses reduces the CO 2 uptake, which ultimately decreases the photosynthetic rate, growth and yield (Bhardwaj et al, 2021;Yin et al, 2023a). Various cotton studies have indicated that the occurrence of drought stress triggers a decrease in photosynthetic rates due to limitations imposed by both stomatal and non-stomatal factors (Cheng et al, 2022;Sultana et al, 2023;Yin et al, 2023b).…”
Section: Introductionmentioning
confidence: 99%
“…It is widely accepted fact that stomatal closure by these stresses reduces the CO 2 uptake, which ultimately decreases the photosynthetic rate, growth and yield (Bhardwaj et al, 2021;Yin et al, 2023a). Various cotton studies have indicated that the occurrence of drought stress triggers a decrease in photosynthetic rates due to limitations imposed by both stomatal and non-stomatal factors (Cheng et al, 2022;Sultana et al, 2023;Yin et al, 2023b).…”
Section: Introductionmentioning
confidence: 99%
“…It is widely accepted fact that stomatal closure by these stresses reduces the CO 2 uptake, which ultimately decreases the photosynthetic rate, growth and yield (Bhardwaj et al, 2021;Yin et al, 2023a). Various cotton studies have indicated that the occurrence of drought stress triggers a decrease in photosynthetic rates due to limitations imposed by both stomatal and non-stomatal factors (Cheng et al, 2022;Sultana et al, 2023;Yin et al, 2023b).…”
Section: Introductionmentioning
confidence: 99%